Comparative Study of Characteristics and Interface States with and without Post‐Gate‐Annealing Treatment for AlGaN/GaN‐Recessed Metal–Insulator–Semiconductor High Electron Mobility Transistors Using HfO2 Gate Insulator on Si Substrates. Issue 6 (12th February 2020) - Zhao, Yaopeng; Wang, Chong; Zheng, Xuefeng; Ma, Xiaohua; He, Yunlong; Liu, Kai; Li, Ang; Peng, Yue; Zhang, Chunfu; Hao, Yue
Abstract : Three types of enhancement‐mode (E‐mode) AlGaN/GaN metal–insulator–semiconductor high electron mobility transistors (MIS‐HEMTs) with different barrier depths are fabricated on Si substrates. A HfO2 gate insulator with a thickness of 30 nm is grown by plasma‐enhanced atomic layer deposition (PEALD) at 300 °C. The drain current density and transconductance increase greatly after post‐gate‐annealing (PGA, 400 °C, 5 min) treatment. The V th of the MIS‐HEMT decreases after PGA treatment and the C – V characteristics are a good match to the V th change of the transfer characteristics. The interface states are in the form of trap states and fixed charges. The trap states at the HfO2 /AlGaN interface are measured by the frequency‐ and voltage‐dependent conductivity method. The trap state density and time constant decrease after the PGA treatment. The fixed charge density can be calculated by the V th shift. According to the calculation results, the fixed charge density also decreases. The PGA treatment can reduce the interface state density effectively and is a significant process for the gate‐recessed MIS‐HEMT. Abstract : Three types of enhancement‐mode (E‐mode) AlGaN/GaN metal–insulator–semiconductor high electron mobility transistors (MIS‐HEMTs) with different barrier depths are fabricated on Si substrates using a HfO2 gate insulator. The current and transconductance increase greatly after post‐gate‐annealing (PGA, 400 °C, 5 min) treatment as the barrier layer becomes thinner. The V th of the MIS‐HEMT decreases after PGA treatment.